Cross-Bridges and Sarcomeric Non-cross-bridge Structures Contribute to Increased Work in Stretch-Shortening Cycles - Tomalka, André; Weidner, Sven; Hahn, Daniel; Seiberl, Wolfgang; Siebert, Tobias (Frontiers in Physiology, 2020)
Stretch-shortening cycles (SSCs) refer to the muscle action when an active muscle stretch is immediately followed by active muscle shortening. This combination of eccentric and concentric contractions is the most important type of daily muscle action and plays a significant role in natural locomotion such as walking, running or jumping. SSCs are used in human and animal movements especially when a high movement speed or economy is required. A key feature of SSCs is the increase in muscular force and work during the concentric phase of a SSC by more than 50% compared with concentric muscle actions without prior stretch (SSC-effect). This improved muscle capability is related to various mechanisms, including pre-activation, stretch-reflex responses and elastic recoil from serial elastic tissues. Moreover, it is assumed that a significant contribution to enhanced muscle capability lies in the sarcomeres itself. Thus, we investigated the force and work produced by single skinned fibres of rat soleus muscles during and after ramp contractions at a constant velocity. Shortening, lengthening, and SSCs were performed under physiological boundary conditions with 85% of the maximum shortening velocity and stretch-shortening magnitudes of 18% of the optimum muscle length. The different contributions of cross-bridge (XB) and non-cross-bridge (non-XB) structures to the total muscle force were identified by using Blebbistatin. The experiments revealed three main results: (i) partial detachment of XBs during the eccentric phase of a SSC, (ii) significantly enhanced forces and mechanical work during the concentric phase of SSCs compared with shortening contractions with and without XB-inhibition, and (iii) no residual force depression after SSCs. The results obtained by administering Blebbistatin propose a titin-actin interaction that depends on XB-binding or active XB-based force production. The findings of this study further suggest that enhanced forces generated during the active lengthening phase of SSCs persist during the subsequent shortening phase, thereby contributing to enhanced work. Accordingly, our data support the hypothesis that sarcomeric mechanisms related to residual force enhancement also contribute to the SSC-effect. The preload of the titin molecule, acting as molecular spring, might be part of that mechanism by increasing the mechanical efficiency of work during physiological SSCs.